Change Leadership in Small Enterprises: Evidence from Singapore - MENKHOFF, Thomas (Institutional Knowledge at Singapore Management University, 2006)
Leading change processes in an enterprise is a challenge for many entrepreneurs. Numerous elements influence the outcomes of such transformation processes, including the adopted change leadership style, the implementation skills of the entrepreneur, the particular scenario of change in terms of urgency of change and resistance, the scale of change as well as macro variables. This article sheds light on the change leadership approaches of small Chinese entrepreneurs in Singapore. It aims at examining widespread common-sense assumptions that æAsianÆ small entrepreneurs adopt mostly directive-coercive (autocratic) change leadership approaches. We argue that there is indeed a great diversity and heterogeneity amongst small firm owners in Asia with regard to their change leadership practices and that the respective change leadership implementation approaches are contingent upon both demographic variables and situational forces such as the urgency of change, the degree of resistance to change and/or the dynamics of the environment in which the firms operate. Data from a SME survey in Singapore (n = 101) serve to substantiate our hypotheses about change leadership in SingaporeÆs SME sector which will have to be systematically tested based on a bigger, representative sample. Key words: change leadership, organizational change, SMEs, Singapore 1 Thanks are due to the Singapore Chinese Chamber of Commerce & Industry (SCCCI) which was instrumental in helping us to conduct the survey, D.S. De Guzman for Figure 1 and Tan Wee Liang (Singapore Management University) for his comments about an earlier version of the paper.